Applesauce weather - Frost, Helen, 1949-; Bates, Amy June (Somerville, Massachusetts : Candlewick Press, 2016)
"When the first apple falls from the tree, Faith and Peter know that it's applesauce weather, even though Peter is getting a little old for such things. It also means Uncle Arthur should be here to tell his stories, with a twinkle in his eye as he spins tales about how he came to have a missing finger. But this is the first year without Aunt Lucy, and when Uncle Arthur arrives, there's no twinkle to be found and no stories waiting to be told. Faith is certain, though, that with a little love and patience, she and Peter might finally learn the truth about that missing finger. Paired with warm, expressive illustrations by Amy June Bates, this heartfelt tale by award-winning poet Helen Frost highlights the strength of family and the power of a good story" --
Keywords: Apples -- Juvenile fiction; Families -- Juvenile fiction; Novels in verse; Nature stories; Children's poetry, American -- Juvenile poetry; Apples -- Fiction; Families -- Fiction; Children's poetry, American -- Fiction; Apples -- Juvenile fiction; Families -- Juvenile fiction; Poetry